Fulfillment of basic needs ”CartMan” as poverty phenomenon in Bandung City - Siti Sofa Fauzia Syah; Siti Anah Kunyati (AMCA, 2024)
The ”Cartman” is a phenomenon of poverty. They work as scavengers to fulfill basic needs daily in Bandung. Basic needs can never be fully met. Cartman makes a living by scavenging rubbish and sleeping in shop windows, and their children take turns sleeping in the cart. The aims of this research are 1) to find out the fulfillment of Cartman's basic needs, 2) to find out how Cartman fulfills their basic needs, and 3) to find out Cartman's daily activities. The research method used in this research is phenomenology. Data collection techniques are done through observation, interviews, and documentation studies. The data analysis technique used is qualitative. The sampling technique used was non-probability with an accidental sampling technique with ten informants. This research shows that basic needs have not been met, such as housing and education, food, clothing, and aspects of meeting clean water and sanitation needs. The activities of the Cartman are only focused on looking for second-hand goods to meet their basic needs, surviving to meet their family's needs, and hoping to get help from the community. The activity of looking for used goods starts from waking up, and the working hours of the Cartman vary.